Load Balancing Metric Based Routing Protocol for Low Power and Lossy Networks (lbRPL) - Sebastian, A; Sivagurunathan, S; ., . (International Journal of Engineering and Technology, 2018)
IETF ROLL working Group standardized the IPv6 Routing protocol (RPL) for applications over low-power and lossy networks (LLNs). RPL constructs a Destination Oriented Direction Acyclic Graph (DODAG) to organize network topology. RPL shows fast network setup and good scalability. However, it may suffer from load imbalance due to diverse network traffic and heavy load on preferred or forwarding parents. To optimize the load balancing of routes in RPL, this paper proposes load balancing metric based routing protocol called lbRPL. We introduce a new routing metric for RPL called load balancing index (LBI), which exploits load balancing characteristics of RPL nodes to select more load balanced parents and routes. LBI includes ETX, Parent count (Pc) and Remaining Parent Energy (Pe) metrics to make routing decisions. Simulation results show that lbRPL improves network performance, stability and improved network life time to RPL.Â Â